Delayed Recovery of the Irminger Interior From Cooling in 2015 Due To Widespread Buoyancy Loss and Suppressed Restratification - Nelson, Monica; Straneo, Fiamma; Purkey, Sarah G.; De Jong, Marieke Femke (Geophysical Research Letters, 2024)
Watermass transformation in the Irminger Sea, a key region for the Atlantic Meridional Overturning Circulation, is influenced by atmospheric and oceanic variability. Strong wintertime atmospheric forcing in 2015 resulted in enhanced convection and the densification of the Irminger Sea. Deep convection persisted until 2018, even though winters following 2015 were mild. We show that this behavior can be attributed to an initially slow convergence of buoyancy, followed by more rapid convergence of buoyancy. This two-stage recovery, in turn, is consistent with restratification driven by baroclinic instability of the Irminger Current (IC), that flows around the basin. The initial, slow restratification resulted from the weak horizontal density gradients created by the widespread 2015 atmospheric heat loss. Faster restratification occurred once the IC recovered. This mechanism explains the delayed recovery of the Irminger Sea following a single extreme winter and has implications for the ventilation and overturning that occurs in the basin. Key Points Widespread buoyancy loss across the Irminger interior and Irminger Current (IC) delayed the recovery of the interior from strong cooling in 2015 Baroclinic instabilities shed from the IC are the dominant source of buoyancy restratifying the sub-surface Irminger interior It is important to consider changes in the IC when considering drivers of variability in convection, ventilation, and the Atlantic Meridional Overturning Circulation Plain Language Summary The Irminger Sea, between Greenland and Iceland, is known to be an important driver of variability in the global ocean circulation that regulates global climate. During the 2015 winter, the Irminger Sea experienced widespread cooling and buoyancy loss down to 1,000 m, resulting in deeper wintertime mixing than had been observed in the region for many years. This low buoyancy state and deep wintertime mixing persisted from 2015 to 2018, despite a return to average atmospheric wintertime conditions. Here we study how ...